ACTIVE AND REACTIVE POWER FLOW OF ISOLATED WIND HYDRO HYBRID SYSTEM BY USING ADAPTIVE FILTER - Sampath, B.Mounika; Jagadeesh, Mr.A. (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
This paper deals with a new isolated wind–hydro hybrid generation system employing one squirrel-cage induction generator (SCIG) driven by a variable-speed wind turbine and another SCIG driven by a constant-power hydro turbine feeding three-phase four-wire local loads.The proposed system consists of back-to-back-connected pulsewidth modulation controlled insulated-gate-bipolar-transistorbased voltage-source converters (VSCs) with a battery energy storage system at their dc link. The proposed wind-hydro hybrid system has a capability of bidirectional active- and reactive-power flow, by which it controls the magnitude and the frequency of the load voltage. The main objectives of the control algorithm for the VSCs are to achieve maximum power tracking (MPT) through rotor speed control of a wind-turbine-driven SCIG under varying wind speeds and control of the magnitude and the frequency of the load voltage.